Culinary Center of Nueva Vizcaya (CuCeNa) revitalization of food culture in Nueva Vizcaya through suro-makan generative architecture - Manzano, Kervin Paul B.; Gines, Leonido Jr. M. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
Food Culture has been an integral aspect of intangible cultural heritage of a locality.
The province of Nueva Vizcaya is home of different indigenous cultural communities
with diverse and vibrant cultures. Their vibrant culture is showcased through their
food culture such as their endemic food, agriculture, hunting and fishing practices,
culinary craftsmanship, rituals and practices, food processing, and even vernacular
architecture. However, with limited documentation and concerns on modernization,
challenges now arise on how to promote and preserve the cultural heritage of the
province. Since culture development can be a driving force for tourism and economic
development, tangible solutions must be provided to safeguard this intangible
cultural heritage. The project will investigate providing an architectural solution that
will revitalize the food culture of Nueva Vizcaya through different design
interventions. Different historical data, interviews, and surveys with the people of
Nueva Vizcaya will strengthen the claim of the province having a diverse food
culture. Through the study of the locality and the users of the space, different tangible
interventions will be gathered to highlight the different aspects of food culture. The
architectural design will promote human-centric experience that generates food
culture knowledge not just for the locals but the visitors of the project as well. With
this project, it will promote the food culture of Nueva Vizcaya and aims to be a
culinary center that preserves the cultural identity of Nueva Vizcaya.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Food culture; Culinary center -- Nueva Vizcaya; Culinary Center of Nueva Vizcaya (CuCeNa)